Clear and present danger standard 100th anniversary: Examining Donald J. Trump's "presidential" rhetoric as a clear and present danger. Issue 1 (2nd January 2021) - Brewer, Edward C.; Egan, Chrys
ABSTRACT: For the past 100 years, the Supreme Court ruling in the case of Schenck v. United States, 249 U.S. 47, from 1919 has stood as a landmark case due to the Court's creation of a "Clear and Present Danger" standard of freedom of speech. Through the vehicle of the Clear and Present Danger measure, the Court reconsidered that the degree of freedom for inflammatory rhetoric could be legally permissible until the point that realistic danger of harm or illegal action might occur. One century after this ruling, this paper examines the unprecedentedly divisive and uncivil public rhetoric of a US President, Donald J. Trump. Through a descriptive analysis summarizing the characteristics of President Trump's rhetoric, we contend that Trump generates a level of dangerous Presidential communication not publicly expressed by previous Presidents that arguably could be considered to overstep the limits of free expression set forth by the courts.